Association Between PaCO2 and Optic Nerve Sheath Diameter in Acute Hypercarbic Respiratory Failure - Munir, Ali Arslan; Abdul Rasheed; Khan, Ahmed Mujadid; Kanza Khalid; Asim Hussain; Hussain, Shabbir (Pakistan Armed Forces Medical Journal, 2026)
Objective: To investigate the relationship between changes in Optic Nerve Sheath Diameter (ONSD), Partial arterial carbon dioxide pressure (PaCO2) and pH in Arterial blood gases (ABGs) in Chronic Obstructive Pulmonary Disease (COPD) patients presenting with acute hypercarbic respiratory failure (AHRF) receiving Non Invasive mechanical ventilation (NIMV).Study Design: Quasi Experimental Study.Place and Duration of study:  Department of Critical Care Medicine, Pakistan Emirates Military Hospital (PEMH), Rawalpindi, Pakistan from Jan to Jun 2025.Methodology: One Hundred patients with COPD were recruited in study having Acute Hypercarbic Respiratory Failure on ABGs requiring Noninvasive mechanical ventilation. Demographic variables, vital signs, conscious level, PaCO2, pH and ONSD were measured prior to initiation of NIMV and in second hour of NIMV.Results: A total of 100 patients with acute hypercarbic respiratory failure were analyzed. After 1 hour of non-invasive ventilation, median PaCO₂ significantly decreased from 64.00 (66.00 – 62.00) mmHg to 50.00 (53.00 – 48.00) mmHg showing a 21.9% reduction (p